Prenatal features of isolated subependymal pseudocysts associated with adverse pregnancy outcome. (8th November 2015) - Esteban, H.; Blondiaux, E.; Audureau, E.; Sileo, C.; Moutard, M. L.; Gelot, A.; Jouannic, J. M.; Ducou le Pointe, H.; Garel, C.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2015; 46: 648–648 ABSTRACT: Objectives: To identify at prenatal ultrasound (US) the features of apparently isolated subependymal pseudocysts (SEPC) that may indicate underlying pathology and should lead to further investigations. Methods: This was a retrospective study of cases with SEPC detected on prenatal US and/or magnetic resonance imaging (MRI). Those with apparently isolated SEPC at US were classified into two groups as follows: Group 1 ( n = 29): normal prenatal US and MRI (except for SEPC) and normal outcome; Group 2 ( n = 12): normal prenatal cerebral US (except for SEPC) and abnormal prenatal cerebral MRI with or without abnormal outcome. A third group ( n = 9) included cases with abnormal prenatal US and MRI. The latter cases with obvious cerebral abnormalities at US were excluded from the statistical analysis as they do not represent a diagnostic dilemma for clinicians. Groups 1 and 2 were analyzed, comparing them with respect to their SEPC characteristics (size, number, location in relation to the caudothalamic notch and the ventricular horns and morphology) and extracerebral abnormalities. Results: The mean ± SD SEPC great axis was longer in Group 2 (11.67 ± 5.82 mm) than it was in Group 1 (8.00 ± 5.64 mm) ( P = 0.021), suggesting an optimal cut‐off for size of SEPC of ≥ 9 mm (sensitivity = 75%, specificity = 62%) to maximize sensitivity for predicting pathological outcome. SEPC adjacent to the temporal horns and SEPC located posterior to the caudothalamic notch were observed more frequently in Group 2, indicating their association with poor outcome ( P = 0.003 and P = 0.003, respectively). Atypical morphology and extracerebral abnormalities were observed more frequently in Group 2 ( P = 0.013 and P = 0.044, respectively). There was no statistically significant difference between groups for either number or location of cysts along the inferior wall or adjacent to the lateral wall of the frontal horns ( P = 0.591 and P = 0.156, respectively). Conclusion: When apparently isolated SEPC are observed at prenatal US, further investigations should be performed under the following circumstances: (1) SEPC great axis ≥ 9 mm; (2) SEPC adjacent to the occipital and temporal horns; (3) SEPC located posterior to the caudothalamic notch; (4) SEPC with atypical morphology. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.